Implementation Financial Records System for Pepper Farmers in Bangka Using Website and Mobile Applications - Rulyanti Susi Wardhani; Ghiri Basuki Putra; Julia Julia (Integrated Journal of Business and Economics (IJBE), 2022)
The pepper plant is a main commodity for farmer in the Bangka city because it has a reasonably high selling power and a distinctive taste also long history. Still, many problems occur because Bangka Belitung has a national and international role, resulting in less and less influence on the economic conditions of pepper farmers, wrong one factor is the lack of use of information technology by pepper farmers in the current era, both for marketing and for financial records. This study aims to build a financial recording system for pepper farmers based on websites and android applications to make it easier for farmers to produce financial documents and become a financial report for farmers and outsiders.  The technique used in this research is the waterfall method, which will facilitate the development of an information framework. This research aims to make applications for pepper farmers in the Province of Bangka Belitung Islands and help financial management. Pepper farmers can utilize information technology for their interests in the industrial era 4.0 and improve information technology expertise in increasing the well fare of pepper farmers